Conditional Threats - Øverland, Gerhard (2010)
Abstract In this paper I ponder the moral status of conditional threats, in particular the extent to which a threatened party would be permitted to use (lethal) defensive force. I first investigate a mugger case before turning briefly to the more complicated issue of national defence in the face of an invading army. One should not exaggerate the level of protection people under threat owe their conditioned killers simply because what is extorted is of little value. After all, either the conditional threat is willing to kill for something she has no claim on at all, or, if she has a just claim on it – or good reason to believe that she has – she is willing to kill to (re)acquire something of not much worth. In both cases the moral culpability of the conditional threat could be seen as reducing her claim on protection from harm.
Keywords: MORAL CULPABILITY; Risk; Responsibility; CONDITIONAL THREATS